Multidisciplinary management and outcome in pancreatic cancer patients treated with high-intensity focused ultrasound. (1st January 2020) - Thudium, Marcus; Bette, Birgit; Tonguc, Tolga; Ghaei, Shiwa; Conrad, Rupert; Becher, Marc U.; Mücke, Martin; Luechters, Guido; Strunk, Holger; Marinova, Milka
Abstract: Introduction: High-intensity focused ultrasound (HIFU) for pancreatic cancer is a growing therapeutic field which has been proven to reduce cancer pain and provide a local tumor control additionally to standard palliative care. However, less is known about the multidisciplinary and especially anesthesiological management of HIFU treatment although an interdisciplinary approach is crucial for treatment success. Material and methods: Anesthesiological and radiological records of 71 HIFU-treated pancreatic cancer patients were analyzed with regard to the following items: intervention time, sonication time, total energy, anesthesia time, peri-interventional medication, body temperature maximum and minimum, pain scores before and 1 day, 6 weeks and 3 months after intervention, peri-interventional complications. Effects on pain scores were estimated with a mixed panel data model. Bivariate associations between interventional variables were examined with the Spearman's correlation. Results: HIFU treatment was performed without major adverse events. Peri-procedural hyperthermia >37.5 °C occurred in 2 patients, hypothermia <35 °C in 8 cases. Interventional variables did not correlate significantly with pain scores, opioid dose, nor body temperature. 85.5% of patients experienced significant early pain relief within the first week after intervention. Post-interventional pain relief is associated with morphine equivalent opioid dose ( p  = 0.025) and treatment time ( p  = 0.040). Conclusion: While HIFU can be considered safe and effective treatment option, procedure-associated pain and temperature management represent challenges for the interdisciplinary HIFU intervention team. Especially short-term pain relief depends on the combined effort of the radiologist and anesthesiologist.